Novel response to neoadjuvant anti-PD1 therapy for a patient with retrocaval melanotic schwannoma. Issue 1 (February 2021) - Vining, Charles C.; Hsu, Phillip J.; Miller, Aaron; Olson, Daniel J.; Gajewski, Thomas F.; Pytel, Peter; Bauer, Bruce S.; Millis, Michael J.; Roggin, Kevin K.
Abstract : Melanotic schwannoma is a rare nerve sheath tumor composed of melanin-producing Schwann cells with the potential for metastasis. These tumors can be associated with familial tumor syndromes and can cause significant symptoms related to nerve compression and mass effect. Due to the rarity of these lesions, they can be initially misidentified as melanocytomas, pigmented dermatofibrosarcoma protuberans, neurofibromas or malignant melanomas. Surgical excision is the mainstay of treatment with limited benefit from adjuvant systemic chemotherapy or radiation. Modern treatments with immune checkpoint blockade have demonstrated significant improvements in progression-free and overall survival for a variety of cancer histologies; however, anti-PD1 therapy has yet to be evaluated in patients with melanotic schwannoma. This report demonstrates a significant improvement in symptomatology and tumor stability with neoadjuvant anti-PD1 therapy for a retrocaval melanotic schwannoma initially masquerading as malignant melanoma. This report demonstrates the potential benefit of a novel therapeutic option for patients with melanotic schwannoma.